2013
DOI: 10.12736/issn.2300-3022.2013204
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of inland navigation on the Vistula from Warsaw to Gdańsk

Abstract: Waterborne transport is the cheapest, the safest and the least harmful to the natural environment. Restoring regular waterway cargo transport will require revitalisation of the existing transshipment and logistics infrastructure for commercial inland ports and building new. Transport policy makers must remember that waterborne transport is the most ecological type of transport. It produces only 10% of the gases emitted to the atmosphere by equivalent road transport. Its energy intensity constitutes 30% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In such a way, Torun may become the city of the river or the city open to the river, a blue and green brand that can bring many tourists to its space and may determine them to spend more time there and enjoy the so-called "water tourism". Our opinion is in accordance with previous studies conducted by Bolt and Jerzylo in 2013 [34] and Nones in 2021 [35] who analyzed the navigation conditions of the lower Vistula water infrastructure, focusing on river ports and the inland waterway fleet. Besides these realistic and important results, in late 2018, Anton et al [19] sustained an old (but never put into practice) challenging idea for inland navigation: a connection between the Baltic and the Black Seas using a navigable route along the Vistula-Prut rivers waterway.…”
Section: Theoretical Backgroundsupporting
confidence: 92%
See 1 more Smart Citation
“…In such a way, Torun may become the city of the river or the city open to the river, a blue and green brand that can bring many tourists to its space and may determine them to spend more time there and enjoy the so-called "water tourism". Our opinion is in accordance with previous studies conducted by Bolt and Jerzylo in 2013 [34] and Nones in 2021 [35] who analyzed the navigation conditions of the lower Vistula water infrastructure, focusing on river ports and the inland waterway fleet. Besides these realistic and important results, in late 2018, Anton et al [19] sustained an old (but never put into practice) challenging idea for inland navigation: a connection between the Baltic and the Black Seas using a navigable route along the Vistula-Prut rivers waterway.…”
Section: Theoretical Backgroundsupporting
confidence: 92%
“…There are also many plans for developing the Lower Vistula (including its Torunian stretch), which should become a navigation link (through the E40 and E70 international European waterways represented in Figure 1) to the rest of Europe [66], along with the potential reactivation of the Lower Vistula Cascade (LVC) project [33,34]. Scientists showed that this transport project of adapting the Lower Vistula River to the International Standards of Waterway Routes will create a 177-181% profit surplus over costs (63.2%-investment costs and 36.8%-maintenance and operation costs), 41.1% of which will be transport profits connected to the environmental protection (reducing the atmosphere pollution, climate change effects, noise congestion etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In light of available knowledge and literature according to problems which could appear during the transport of cargo on inland waterways [18,20,28] challenges us to demonstrate the possibility of non-standard load transport on waterways with a shallow channel bed such as the Vistula River in Poland. The main objective of the research was to develop a comprehensive toolkit for preliminary analysis of the safety conditions for oversized cargo transport on waterways with a shallow riverbed.…”
Section: Introductionmentioning
confidence: 99%